Bangalore tiger how Indian tech upstart Wipro is rewriting the rules of global competition - Hamm, Steve (McGraw-Hill, 2007)
Of all the tech tigers in India, Wipro is one of a handful that stands out from the pack. In the past five years, it has become one of the most accomplished tech services providers in the world. Wipro is known to go above and beyond to make customers happy--a move that's paid off handsomely. From the story of Wipro's transformation and its impact on the tech services industry and the rules of global competition, journalist Hamm mines a treasure of business lessons. He also provides a rare glimpse into the mind of Wipro's charismatic leader, Azim Premji, one of the first business leaders in India to decree that his company would not pay bribes. You'll see how his adoption of world-class business processes helped Wipro thrive--and how Wipro is helping to fulfill his dream of a better educated, more prosperous India.--From publisher description.
Includes index.
Keywords: Wipro Corp. (India); Nouvelles technologies de l'information et de la communication - Inde; Technologie de pointe - Inde; High technology services industries -- India; Information technology -- India; Customer services -- India; Business logistics -- India; Indien